Nonantibiotic treatments for urinary cystitis: an update. Issue 6 (November 2020) - Barea, Bianca M.; Veeratterapillay, Rajan; Harding, Chris
Abstract : Purpose of review: Urinary tract infections (UTIs) are one of most common infections in everyday clinical practice. Given the increase in antimicrobial therapy resistance, there has been an increased interest in nonantibiotic treatment options for common infections. Recent findings: A review of the recent literature including on nonantibiotic options for management of UTIs, symptoms of cystitis and prevention of recurrent UTIs. Summary: The article provides an overview on alternative therapy to antibiotics in the treatment of cystitis and recurrent UTI prophylaxis, including alkalinization of urine, cranberry products, probiotics, NSAIDS, D-mannose, herbal medicine, methenamine hippurate, oral immunostimulants (immunotherapy), topical oestrogens, vitamins and acupuncture. The last few years of intense research has focused on an effort to find evidence to corroborate potentially efficacious non antibiotic treatments. However, alternative treatments for UTIs have not brought conclusive evidence that antibiotic usage can be replaced completely by nonantibiotic options. The reason for this is largely due to a lack of good-quality randomized controlled trials on this subject.